Фізична форма жінок, котрі поступають на реабілітацію на курорт Трускавець, та її гемодинамічні, гормональні і метаболічні фактори - Флюнт, І.С.; Величко, Л.М.; Журавчак, Т.А.; Гривнак, Р.Ф.; Ганик, Л.М.; Тимочко, О.Б. (Медична гідрологія та реабілітація, 2010)
Констатировано широкое разнообразие уровня физической формы по 5-балльной шкале Astrand у женщин, прибывающих на курорт Трускавец на реабилитацию после холецистэктомии: неудовлетворительный - у 15,5%, удовлетворительный - у 64% и хороший - у 20,5%. Методом корреляционного анализа выявлены как положительные (уровень в плазме эстрадиола, холестерина альфа-липопротеидов, трийодтиронина, магния, в эритроцитах - натрия), так и отрицательные (артериальное давление, уровень в плазме кортизола, триацилглицеридов, тиротропного гормона, уратов и активность Mg-АТФазы мембран эритроцитов) актотропные факторы, которые в совокупности детерминируют уровень физической формы на 55%. Ascertained wide variety of fitness level on a 5-point scale Gstrand in women who arrive at Truskavets for rehabilitation after cholecystectomy: inadequate - in 15,5%, satisfactory - in 64% and good - in 20,5%. The method of correlation analysis revealed both positive (levels in plasma estradiol, cholesterol of alpha-lipoproteines, triiodothyronine, magnesium and in erythrocytes - sodium) and negative (blood pressure, levels in plasma cortisol, triacylglicerides, TTH, urates and Mg-ATPase activity erythrocyte membranes) actotropic factors which together determine the level of physical fitness by 55%.